Case Report: Catheter rupture of central venous port devices placed via the right internal jugular vein for chemotherapy in gastrointestinal cancer patients: a four-case series - Tanaka, Toshimitsu; Masaru, Fukahori; Nagasu, Sachiko; Kuhara, Asako; Koganemaru, Masamichi; Tanoue, Shuichi; Fujita, Fumihiko; Kawaguchi, Takumi; Miwa, Keisuke (Frontiers in Oncology, 2025)
BackgroundCentral venous (CV) ports are extensively employed for the administration of chemotherapy in cancer patients owing to their safety and reliability. The rupture of a CV port catheter is an infrequent occurrence; nonetheless, it can effectuate serious complications if left untreated. In this case series, we present four cases of catheter rupture of CV ports implanted in cancer patients via the right internal jugular vein for chemotherapy administration.ResultsOur series comprised one male and three female patients, with an age range of 41–76 years (median age: 61 years). All CV ports were implanted through the right internal jugular vein using a PowerPort® MRI device and were placed for a median duration of 39 months (range: 17–45 months). In three of four instances, CV ports were inactive at the time of catheter rupture; nevertheless, one study participant continued to use the CV port even after it had ruptured. None of the patients presented with any subjective symptoms at the time of catheter rupture. Two cases were detected via subcutaneous tissue swelling during CV port utilization, and the other two were incidentally detected via imaging. The ruptured catheters were located in the right atrium-right ventricle in two patients and in the superior vena cava and left pulmonary artery in the third and fourth patients, respectively. All four devices were retrieved without complications using a snare catheter.ConclusionCatheter rupture of the CV port is a rare but potentially grave complication. Therefore, routine monitoring is required, considering the possibility of catheter rupture if the CV port is retained as an implant for an extended period.